Correlation of critical current density to quasi-biaxial texture and grain boundary cleanliness in fully dense Bi-2212 wires. (2nd February 2021) - Oloye, T A; Matras, M; Jiang, J; Hossain, S I; Su, Y; Trociewitz, U P; Hellstrom, E E; Larbalestier, D C; Kametani, F
Abstract: The distinctive quasi-biaxial texture of Bi2 Sr2 CaCu2 O x (Bi-2212) plays an important role in enabling high critical current density ( J c ) in Bi-2212 round wires (RWs). Here we studied three over pressure heat treated wires with J c varying by a factor of ∼10, all being fully dense. Using electron backscatter diffraction, we observed the differences in biaxial texture in these three wires. Transmission electron microscopy also revealed differences in grain boundary (GB) cleanliness and connectivity. These analyses showed that high J c is unambiguously correlated to the best biaxial texture, which is in turn correlated to slow cooling from the liquid melt into solid Bi-2212. However, at 4.2 K, there is a negligible difference in intragrain pinning in the three wires, suggesting that the J c variation by a factor of ∼10 is primarily due to variable filament and intergrain connectivity. The principal determinants of intergrain connectivity is the quasi-biaxial texture and GB cleanliness. Overall, J c optimization of the Bi-2212 RW is a complex multi-variable process, but this study shows that maximizing the biaxial texture quality is an important first step in such an optimization process.